Asymmetric Extraction Treatment in a Middle-Aged Patient with Dental Crowding and Protrusion using Clear Aligners - Xiujin Xing; Hanglin Qin; Jing Sun; Kun Li (Hindawi Limited, 2023)
Frequently, orthodontic treatment involves symmetrically extracting premolars to correct severe crowding or protrusion. Nevertheless, in some cases, a more reasonable alternative may be to remove teeth with poor prognoses to improve protrusion and relieve crowding. A middle-aged woman sought treatment for dental protrusion and crowding. Her mandibular right first molar had been treated with root canal therapy due to pulpitis, but she still felt uncomfortable. In addition, her maxillary left second premolar had become carious. Extractions of the maxillary right first premolar and left second premolar, as well as mandibular right first molar and left first premolar were chosen to resolve the occlusion problems. The patient opted for clear aligners on the demands of esthetics as well as comfort. Following orthodontic treatment, the patient attained properly aligned teeth, a pleasing smile, and a facial profile that exhibited greater harmony. This case report demonstrates that, under proper planning, clear aligners are capable of handling challenging cases, including those involving middle-aged individuals and molar extractions.